Marketing wewnętrzny jako metoda motywowania personelu w sektorze usług hotelarskich - Nawrocka, Elżbieta (Personal Marketing as the Staff Motivating Method in the Sector of Hotel Services, 2008)
The broadly understood way of motivating staff presents an extremely important factor influencing efficient functioning of an economic entity, apart from the correct choice of both the mission and goals of an enterprise. Modern management offers diversified solutions, including e.g. work-life-balance or personal marketing. The objective of the hereby article is to present the concept of personal marketing as the method for motivating staff and its significance for effective functioning of an enterprise. The first part of the article discusses potential opportunities for the application of modern staff motivation methods and their effects. The second part presents adequate study results. For the purposes of empirical verification a questionnaire analysis was carried out, at the end of 2006, within the sample consisting of 30% of hotels in Lower Silesia region. On this basis it can be concluded that in the hotel industry sector the principles of personal marketing were implemented to a small extend, the reason for which are weak backgrounds and lack of complex application means. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 378-388